ECOLOGICAL AND ECONOMIC ASPECTS OF THE TRANSITION TO THE “GREEN” ECONOMY IN UKRAINE - V. Shtets (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The ecological and economic situation in Ukraine is analized, preconditions for the emergence and development of the concept of “green economy” as a component of sustainable development are studied and ecological and economic aspects of the transition to it in Ukraine in conditions of climate change are considered.